The rare allele of DGKZ SNP rs10838599 is associated with variability in HDL-cholesterol levels among severely obese patients. Issue 3 (2016) - Bégin, Stéphanie; Guenard, Frederic; Tchernof, Andre; Perusse, Louis; Hould, Frederic-Simon; Lebel, Stefane; Marceau, Picard; Guénard, Frédéric; Vohl, Marie-Claude
No abstract available